Hosting capacity assessment of heat pumps and optimised electric vehicle charging on low voltage networks. (15th September 2021) - Edmunds, Calum; Galloway, Stuart; Dixon, James; Bukhsh, Waqquas; Elders, Ian
Abstract: The decarbonisation of heat and transport using heat pumps (HPs) and electric vehicles (EVs) will require significant investment in low voltage (LV) networks both in terms of network reinforcement and in the provision of flexibility to avoid network upgrades where appropriate. In this paper, a heuristic methodology is presented to estimate headroom available for domestic EV charging optimisation in LV networks at different penetrations of HPs and a novel zonal approach is applied to EV optimisation. It was found that optimised charging of EVs can allow for a significantly higher penetration of EVs for a given HP penetration within the network, without the need for reinforcement. Significant improvements in terms of network hosting capacity were realised: for example, an increase from 34% EV and 50% HP penetration for dumb charging to 72% EV and 57% HP penetration for optimised charging was available for one particular case study. The level of improvement in hosting capacity was found to be strongly dependent on particular network topology and pre-existing demand; this reinforces the need for further study in unlocking the potential synergies of EV and HP uptake. Highlights: Heat pump and optimised electric vehicle capacity assessed on low voltage networks. Novel 'zonal' probabilistic headroom optimisation for electric vehicle charging. Method enables up to two times more electric vehicles than uncoordinated charging. Tractable method for congestion management on low voltage networks. Hosting capacity strongly dependent on network topology and pre-existing demand.